FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN UNINTENDED PREGNANCY PADA REMAJA - Lidya Yulanda Sari; Lutfi Nurdian Asnindari (Universitas Aisyiyah Yogyakarta, 2017)
Abstract: This research aims to study factors related to the event unintended pregnancy adolescent. The analysis used is the chi square test. Results of research on the variable level of knowledge about the unintended pregnancy in the case group and 46.7% less category 66.7% of control group both categories. In variable teenage promiscuity the majority of the cases 86.7% less category, 40% of the control group both categories. In variable parenting parents, the majority of the cases 66.7% less category, 73.3% of the control group both categories. In the variable of mass media, the majority of the cases 14% less diverse categories, 33.3% of control group is very diverse categories. There is a relationship between the level of knowledge, relationships teens, parenting parents, and the media with a value of ñ value (0.000) <á (0.05). Keywords: knowledge, relationships, parenting, media, events unintended pregnancy